2016
DOI: 10.1371/journal.pone.0144200
|View full text |Cite
|
Sign up to set email alerts
|

A Probabilistic Atlas of Diffuse WHO Grade II Glioma Locations in the Brain

Abstract: Diffuse WHO grade II gliomas are diffusively infiltrative brain tumors characterized by an unavoidable anaplastic transformation. Their management is strongly dependent on their location in the brain due to interactions with functional regions and potential differences in molecular biology. In this paper, we present the construction of a probabilistic atlas mapping the preferential locations of diffuse WHO grade II gliomas in the brain. This is carried out through a sparse graph whose nodes correspond to clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 48 publications
3
36
0
Order By: Relevance
“…Previous studies on the distribution of molecular subtypes in gliomas have used a lobe-oriented approach that does not necessarily reflect the stem-cell theory of origin in gliomas [1]. Even so, it has been shown that LGGs in general are preferentially located near the insula [22] and are rarely found in the posterior regions of the brain [23,24]. IDH-mutated gliomas are more often located in the frontal lobes, specifically around the rostral extension of the lateral ventricles [25][26][27], a location also seen in IDHmutated glioblastomas [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on the distribution of molecular subtypes in gliomas have used a lobe-oriented approach that does not necessarily reflect the stem-cell theory of origin in gliomas [1]. Even so, it has been shown that LGGs in general are preferentially located near the insula [22] and are rarely found in the posterior regions of the brain [23,24]. IDH-mutated gliomas are more often located in the frontal lobes, specifically around the rostral extension of the lateral ventricles [25][26][27], a location also seen in IDHmutated glioblastomas [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Such atlases have enabled more accurate automated segmentations, as they contain information regarding the expected locations of tumours across entire patient populations 46 . Applications of probabilistic atlases include segmenting brain MRI for locating diffuse low-grade glioma 50 , prostate MRI for volume estimation 51 and head and neck CT for radiotherapy treatment planning 52 , to name a few.…”
Section: Impact On Oncology Imagingmentioning
confidence: 99%
“…According to the World Health Organization (WHO) scheme, it represents a heterogeneous group of diseases with different degrees of malignancy from relatively indolent diffuse astrocytomas to highly aggressive glioblastoma multiforme (GBM) (1). Among these tumors, grade II astrocytomas are characterized by low level proliferative activity, but often recur, and some of the types tend to progress to higher grades of malignancy (1,2). The prognosis of patients with GBM, the most malignant astrocytoma, remains rather dismal.…”
Section: Introductionmentioning
confidence: 99%